Advancing Gender Equality in Agrifood Systems: A Critical Workshop on the Scaling Readiness of the Gender Norms Measurement Toolkit - Msita, Sarah (CGIAR System Organization, 2024)
On June 19, 2024, a consortium of experts and stakeholders dedicated to advancing gender equality, youth empowerment, and social inclusion within agrifood systems convened at the White Sands Hotel in Dar es Salaam, Tanzania. The gathering aimed to evaluate the scaling readiness of the Gender Norms in Agrifood Systems Measurement Toolkit. Developed by the CGIAR Gender Equality Initiative, HER+, this toolkit provides essential guidance for researchers, planners, and implementers aiming to address gender inequities and transform social norms within the agricultural and food security sectors.